Urgensi Manajemen Strategik dalam Lembaga Pendidikan: (Implementasi di MAN 3 Yogyakarta) - Umar Sidiq (Tarbiyah Departement collaboration with AMCA, 2015)
Empirically that strategic planning can be useful help to assert focus on things that are really important, given the ease of the organization in determining priority activities, optimizing the efficiency of the organization, provide support for the establishment of smooth communication in explaining the purposes of the strategy, help in garnering support from internal and external stakeholders, helping terkristalisasinya a better understanding of the impact that may arise against its decisions in the future and improve coordination among the various activities and various units. As an educational institution, man 3 Yogyakarta has a vision that will drive the future of the madrassa. The concept of vision is something that is very important in management education. The vision of man 3 Yogyakarta is superior and skilled and mature personality that is shortened with an ultra prime.